ANALISIS FAKTOR PENDORONG PELAKSANAAN STANDAR PROSEDUR OPERASIONAL (SPO) DALAM PEMBERIAN OBAT OLEH PERAWAT DI INTENSIVE CARE UNIT (ICU) RUMAH SAKIT UNIVERSITAS AIRLANGGA - Ria Asti Septianti; Djazuly Chalidyanto (Poltekkes Kemenkes Surabaya, 2016)
Medication errors in Intensive Care Unit (ICU) in the Airlangga University Hospital were increased 32% during 2014-2015. The objective of the study was to analyze motivating factor of the implementation of the Standard Operational Procedure (SOP) in drug delivery by nurse in ICU in the Airlangga University Hospital. This study was a descriptive with cross sectional study design. Subjects were selected by total sampling. The result that ICU nurses don’t know and understand about the type, content, and functionality of SOP in drug delivery, supervision by the hospital to the implementation of the SOP in drug delivery is good, and assessment of the ICU nurses about the creation, socialization, implementation, monitoring, and evaluation of SOP in drug delivery is not appropriate. The conclusion is ICU nurses don’t know and understand about the type, content, and functionality of SOP in drug delivery, supervision by the hospital to the implementation of the SOP in drug delivery is good, and assessment of the ICU nurses about the creation, socialization, implementation, monitoring, and evaluation of SOP in drug delivery is not appropriate. Keywords: motivating factor, SOP in drug delivery, ICU nurses